2019
DOI: 10.3390/jcm8050605
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Complications and Hemodynamic Changes Following Intrauterine Interventions for Twin-to-Twin Transfusion Syndrome in Monochorionic Diamniotic Twin Pregnancies

Abstract: Twin-to-twin transfusion syndrome (TTTS) is a challenging complication in monochorionic diamniotic (MCDA) twins. Intrauterine interventions, such as fetoscopic laser ablation and cord occlusion followed by amniodrainage, are established treatments. Little is known about maternal complications and hemodynamics following these interventions. We performed a retrospective analysis of maternal procedure-related complications and the impact of such procedures on maternal hemodynamics and blood characteristics. Withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In a previous study, we observed that high volume amniodrainage was significantly correlated with maternal hemodilution and hemodynamic alterations [ 5 ]. We could confirm those findings in the current prospective cohort, by demonstrating a drop in hemoglobin concentration and hematocrit in the absence of clinical blood loss, suggesting an expansion of blood volume by 18.0 ± 7.0 % (Hct).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we observed that high volume amniodrainage was significantly correlated with maternal hemodilution and hemodynamic alterations [ 5 ]. We could confirm those findings in the current prospective cohort, by demonstrating a drop in hemoglobin concentration and hematocrit in the absence of clinical blood loss, suggesting an expansion of blood volume by 18.0 ± 7.0 % (Hct).…”
Section: Discussionmentioning
confidence: 99%
“…FLA was performed in a standardized fashion as previously described [ 5 ]. All FLA procedures were completed by amniodrainage from the recipient‘s amniotic sac until a DVP of about 6 cm was achieved.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The best treatment for twin-twin transfusion syndrome (TTTS) is fetoscopic laser coagulation of the vascular anastomoses, preferably using the Solomon laser technique [2]. Greimel et al show that this surgical intervention is safe and rarely associated with maternal procedure-related complications [3]. Importantly, TTTS should not be viewed as a homogeneous disorder and may coexist with selective fetal growth restriction (sFGR) and/or twin anemia-polycythemia sequence (TAPS).…”
Section: Twin-twin Transfusion Syndrome (Ttts)mentioning
confidence: 99%